Alpha-neurexins in health and disease - Chofflet, Nicolas; Wang, Manni; Chofflet, Mathilde; Takahashi, Hideto (Frontiers in Molecular Neuroscience, 2025)
Alpha-neurexins (α-Nrxns) are synaptic adhesion molecules that play crucial roles in synapse organization, specificity, and function. This review provides a comprehensive overview of α-Nrxns, covering their gene organization, molecular architecture, and roles in both physiological and pathological contexts. We begin by detailing the unique structural properties of α-Nrxns, particularly their large extracellular regions and complex alternative splicing, which facilitate diverse trans-synaptic interactions. We then examine their critical roles in regulating presynaptic neurotransmitter release, postsynaptic receptor function, and overall synaptic organization. While deletion of α-Nrxns in mice results in only modest morphological brain abnormalities, it causes profound deficits in synaptic function, underscoring their role in fine-tuning neural circuit activity in a context-dependent manner. We also explore how specific α-Nrxn ligands such as neurexophilins or IgSF21 contribute to synaptic diversity. Furthermore, we discuss emerging evidence linking α-NRXNs to various neurodevelopmental and psychiatric disorders, including autism spectrum disorder, schizophrenia, and intellectual disability. These links are supported by both genetic association studies and behavioral analyses in α-Nrxn mutant mice, which exhibit phenotypes that partially mirror symptoms observed in human disorders. Finally, we highlight recent advances in human induced pluripotent stem cell (hiPSC)-derived neuronal models, which offer powerful platforms to investigate α-NRXN-associated disease mechanisms at the cellular level. These models enable the study of patient-specific neurobiological alterations and support the development of targeted therapeutic strategies. Collectively, this review emphasizes the pivotal role of α-Nrxns in maintaining synaptic integrity and demonstrates how their dysfunction contributes to a broad spectrum of brain disorders, providing valuable insights for future translational research.